(untitled) (Journal of Science and Technology, 2016)
This theoretical paper considers mandated cost shifting as a way of providing care for the poor. The method is similar to user fee health care systems with exemption policies for the poor. In the model, the government mandates the proper treatment of illness regardless of the ability to pay, and enforces that mandate with investigation. The results show that under costly investigation the physician randomly cheats by providing the wrong treatment to some types of patients. In response, the government also randomly investigates the treatment of such patients. The results also showed that cost shifting, hence user fee, deteriorates the welfare of both the rich and the poor as investigation becomes costly.